Antimicrobial peptide capsids of de novo design. Issue 1 (December 2017) - Santis, Emiliana; Alkassem, Hasan; Lamarre, Baptiste; Faruqui, Nilofar; Bella, Angelo; Noble, James; Micale, Nicola; Ray, Santanu; Burns, Jonathan; Yon, Alexander; Hoogenboom, Bart; Ryadnov, Maxim
Abstract The spread of bacterial resistance to antibiotics poses the need for antimicrobial discovery. With traditional search paradigms being exhausted, approaches that are altogether different from antibiotics may offer promising and creative solutions. Here, we introduce a de novo peptide topology that—by emulating the virus architecture—assembles into discrete antimicrobial capsids. Using the combination of high-resolution and real-time imaging, we demonstrate that these artificial capsids assemble as 20-nm hollow shells that attack bacterial membranes and upon landing on phospholipid bilayers instantaneously (seconds) convert into rapidly expanding pores causing membrane lysis (minutes). The designed capsids show broad antimicrobial activities, thus executing one primary function—they destroy bacteria on contact. With the growing threat of antibiotic resistance, unconventional approaches to antimicrobial discovery are needed. Here, the authors present a peptide topology that mimics virus architecture and assembles into antimicrobial capsids that disrupt bacterial membranes upon contact.